High-Throughput Sequencing-Guided Development and Validation of an RT-dPCR Assay for Sensitive Detection of Lentinula edodes Spherical Virus in Shiitake Mushrooms - Min-Jae Kim; Chae-Min Kang; In-Gyeong Kim; Rae-Dong Jeong (Current Microbiology, 2026)

First report of lily symptomless virus infecting Digitalis purpurea in Korea - Min-Jae Kim; Ju-Ho Bae; Hyo-Jeong Lee; Rae-Dong Jeong (Journal of Plant Pathology, 2026)

4’-Thionucleosides as adenosine A3 receptor ligands: a medicinal chemistry perspective - Hong-Rae Kim; Lak Shin Jeong (Medicinal Chemistry Research, 2026)

Design, presence, and perception: An exploratory path analysis of nighttime safety perceptions in urban parks - Jong Rae Kim; Poo Reum Jeong; Jeong Moon Kim (Urban Forestry & Urban Greening, 2026)

Pilot-scale microbial electrolysis (MEC) of food waste: Operational impacts of microbial community dynamics and membrane fouling on hydrogen production - Hwi Jong Jung; Sahng Hyuck Woo; Danbee Kim; Yuri Kim; Jiye Lee; Min Su Noh; Jae Woo Jeong; Jung Rae Kim; Minsoo Kim; Chang Hyun Ko; Soo Youn Lee (Chemical Engineering Journal, 2026)

Waterborne Plant Virus Contamination in Major Korean Rivers and its Potential Risks to Agriculture and Environmental Health - Ga-Eun Lee; Min-Jae Kim; Rae-Dong Jeong (Water, Air, & Soil Pollution, 2026)

First report of lily symptomless virus infecting scarlet geranium (Pelargonium inquinans) in Korea - Min-Jae Kim; Hyo-Jeong Lee; Sang-Yun Cho; Rae-Dong Jeong (Journal of Plant Pathology, 2026)

First report of impatiens necrotic spot virus infecting Acalypha australis in Korea - Gwang-Ho Yeom; Min-Jae Kim; Rae-Dong Jeong (Journal of Plant Pathology, 2025)

β–phase polymer-driven enhanced powder flowability and microstructure uniformity for stable and fast dry-processed electrode - Min Jang; Hyeongseok Shim; Sijeong Park; Hyeju Shin; Jeong-Rae Jo; Wooyoung Jin; Hyungyeon Cha; Jung Hoon Kim; Joong Tark Han; Gyujin Song; Sinho Choi (Chemical Engineering Journal, 2025)

First report of euphorbia ringspot virus infecting Euphorbia milii in Korea - Ji-Min Kang; Min-Jae Kim; Rae-Dong Jeong (Journal of Plant Pathology, 2025)

First report of lily symptomless virus in Inula japonica displaying leaf curling and distortion - Min-Jae Kim; Hyo-Jeong Lee; Rae-Dong Jeong (Journal of Plant Pathology, 2025)

The Complete Mitochondrial Genome of the Korean Endemic Polychaete Phyllodoce koreana (Lee & Jae, 1985) from Jindong Bay, Korea, with Additional Morphological and Ecological Features - Dae-Hun Kim; So Jin Ryu; Jong Rae Kim; Seong-il Eyun; Man-Ki Jeong (Journal of Marine Science and Engineering, 2025)
Phyllodoce koreana was first described in 1985 in Gwangyang Bay, a semi-enclosed bay in Korea affected by significant organic input from the Seomjin River and dredging activities near the Gwangyang Port. Since then, this Korean endemic species has received limited attention in taxonomic and ecological studies. Phyllodoce koreana is known for its resilience to mild disturbances but is vulnerable to severe environmental changes. In this study, P. koreana specimens were collected from organically polluted Asian stalked tunicate aquaculture farms at eight sites in Jindong Bay, a location with environmental conditions similar to those of Gwangyang Bay, over the course of five sampling events from March to November. Both bays experience benthic hypoxia in summer due to elevated water temperatures and organic matter accumulation. Phyllodocid specimens were primarily collected in March and November 2023, non-hypoxic periods, suggesting potential seasonal adaptations to environmental fluctuations. The morphological features of the collected specimens were consistent with the original description of P. koreana, confirming their identification. Additionally, we reported previously overlooked morphological details, contributing to a more comprehensive taxonomic understanding of the species. We also present, for the first time, the complete mitochondrial genome of this species, comprising 15,559 bp, which provides essential genetic data for future taxonomic and phylogenetic studies. The phylogenetic analysis of protein-coding genes shows that, among 17 related polychaete species, P. koreana (family Phyllodocidae) is closely related to the family Goniadidae. Future research should expand our knowledge of polychaete taxonomy by integrating additional mitochondrial genomes and investigating the role of conserved gene synteny within Polychaeta.

First report of cucumber mosaic virus causing leaf mosaic and distortion on Arthraxon hispidus in Korea - Min-Jae Kim; Eun-Ji Choi; Rae-Dong Jeong (Journal of Plant Pathology, 2025)

First report of natural infection of Sinapis arvensis by turnip mosaic virus in Korea - Min-Jae Kim; Rae-Dong Jeong (Journal of Plant Pathology, 2024)

First report of narcissus yellow stripe virus in Narcissus pseudonarcissus in Korea - Hae-Jun Kim; Rae-Dong Jeong (Journal of Plant Pathology, 2024)

First report of hoya necrotic spot virus in Hoya kerrii in Korea - Hae-Jun Kim; Rae-Dong Jeong (Journal of Plant Pathology, 2024)

Corrigendum to “Variations of oxidative potential of PM2.5 in a medium-sized residential city in South Korea measured using three different chemical assays” [920 (2024) 171053] - Pyung-Rae Kim; Sung-Won Park; Young-Ji Han; Myong-Hwa Lee; Thomas M. Holsen; Cheol-Heon Jeong; Greg Evans (Science of The Total Environment, 2024)

Variations of oxidative potential of PM2.5 in a medium-sized residential city in South Korea measured using three different chemical assays - Pyung-Rae Kim; Sung-Won Park; Young-Ji Han; Myong-Hwa Lee; Thomas M. Holsen; Cheol-Heon Jeong; Greg Evans (Science of The Total Environment, 2024)

Alginate-encapsulated biochar as an effective soil ameliorant for reducing Pb phytoavailability to lettuce (Lactuca sativa L.) - Hyuck Soo Kim; Yeon Kyu Lee; Byung Jun Park; Ji Eun Lee; Seok Soon Jeong; Kwon Rae Kim; Sung Chul Kim; M. B. Kirkham; Jae E. Yang; Kye-Hoon Kim; Jung-Hwan Yoon (Environmental Science and Pollution Research, 2024)

Genome assembly and microsatellite marker development using Illumina and PacBio sequencing in Persicaria maackiana (Polygonaceae) from Korea - Kang-Rae Kim; So Young Park; Heesoo Kim; Jiyeon Kim; Jeong Min Hong; Sun-Yu Kim; Jeong-Nam Yu (Genes & Genomics, 2024)

First report of natural infection of Vigna angularis by hop stunt viroid in Korea - Chae-Min Kang; Hae-Jun Kim; Rae-Dong Jeong (Journal of Plant Pathology, 2024)

Facile and rapid fabrication of wearable biosensors via femtosecond laser-directed micro-patterning with large-sized reduced graphene oxide for physiological monitoring - Hae-In Moon; Sungil Kim; Jeong Eun Byun; Young Won Kim; Yeon Wook Jung; Seung Geun Jo; Yujin Shin; Yeoul Kang; Sang Jun Kim; Eun-Su Lee; Hyung-Jong Lee; Min-Cheol Oh; et al. (Chemical Engineering Journal, 2024)

Metabolomic analysis reveals linkage between chemical composition and sensory quality of different floral honey samples - Min Jeong Kang; Keup-Rae Kim; Keono Kim; Aria G. Morrill; Chuleui Jung; Sukjun Sun; Dong-Hee Lee; Joon Hyuk Suh; Jeehye Sung (Food Research International, 2023)

First report of Corydalis speciosa Maxim. being a natural host plant for cucumber mosaic virus in Korea - Ye-Yeong Kim; Tae-Seon Park; Ji-Soo Park; Dong-Joo Min; You-Seop Shin; Hyeong-Woo Lee; Rae-Dong Jeong; Jin-Sung Hong (Journal of Plant Pathology, 2023)

First report on natural infection of Nepenthes alata by pepper mild mottle virus in Korea - Ga-Eun Lee; Hae-Jun Kim; In-Sook Cho; Rae-Dong Jeong (Journal of Plant Pathology, 2023)

Incipient subsidence and subsequent clockwise rotation of the Miocene Janggi onshore basin, SE Korea, associated with the back-arc opening of East Sea - Min-Cheol Kim; Rae-Yoon Jeong; Gyeonggeol Gahng; Yong-Un Chae; Cheol Woo Song; Hee-Cheol Kang; Moon Son (Marine Geophysical Research, 2023)

First report of natural infection of Hydrangea macrophylla by pepper mild mottle virus in Korea - Sung-Woong Kim; Ga-Eun Lee; Hyo-Jeong Lee; Hae-Jun Kim; Kwang-Yeol Yang; Rae-Dong Jeong (Journal of Plant Pathology, 2023)

Importance of biochar as a key amendment to convert rice paddy into carbon negative - Ronley C. Canatoy; Seung Tak Jeong; Song Rae Cho; Snowie Jane C. Galgo; Pil Joo Kim (Science of The Total Environment, 2023)

First report of pitaya virus X infecting dragon fruit (Selenicereus undatus) in Korea - Nam-Yeon Kim; Yong Hun Jo; Young Min Bae; Kyung-Pyo Lee; Rae-Dong Jeong; Yeon Soo Han; KiBeom Park (Journal of Plant Pathology, 2023)

First report of cucumber mosaic virus infecting Ocimum basilicum in Korea - Ga-Eun Lee; Hae-Jun Kim; Hyo-Jeong Lee; Sena Choi; Rae-Dong Jeong (Journal of Plant Pathology, 2023)

Expansion of Human Megakaryocyte-Lineage Progeny via Aryl Hydrocarbon Receptor Antagonism with CH223191 - Dongchan Kim; Dong-Yeop Shin; Jun Liu; Na-rae Jeong; Youngil Koh; Junshik Hong; Xinxin Huang; Hal E. Broxmeyer; Sung-Soo Yoon (Stem Cell Reviews and Reports, 2022)

First report of zucchini yellow mosaic virus infecting wax begonia (Begonia semperflorens) in Korea - Sung-Woong Kim; Seong-Gyeong Kim; Hyo-Jeong Lee; Kwang-Yeol Yang; Rae-Dong Jeong (Journal of Plant Pathology, 2022)

First report of natural infection of Jatropha integerrima by pepper mild mottle virus in Korea - Hae-Jun Kim; Hyo-Jeong Lee; Hyeong Woo Lee; Jin-Sung Hong; Rae-Dong Jeong (Journal of Plant Pathology, 2022)

First report of natural infection of Dracaena braunii by pepper mild mottle virus in Korea - Sung-Woong Kim; Yujin Jeong; Kwang-Yeol Yang; Rae-Dong Jeong (Journal of Plant Pathology, 2022)

Tomato ARPC1 regulates trichome morphology and density and terpene biosynthesis - Jae-In Chun; Seong-Min Kim; Na-Rae Jeong; Sang Hee Kim; Choonkyun Jung; Jin-Ho Kang (Planta, 2022)

First report of tomato spotted wilt virus infecting Epipremnum aureum in Korea - Hyo-Jeong Lee; Seong Woong Kim; Na-Kyeong Kim; Kwang-Yeol Yang; Rae-Dong Jeong (Journal of Plant Pathology, 2022)

First report of tomato spotted wilt virus infecting parlor palm (Chamaedorea elegans) with leaf mosaic and ring spot disease in Korea - Hyo-Jeong Lee; Na-Kyeong Kim; Su-Yeon Hwang; Kwang-Yeol Yang; Rae-Dong Jeong (Journal of Plant Pathology, 2022)

First report of zucchini yellow mosaic virus infecting balloon flower (Platycodon grandiflorus) in Korea - Na-Kyeong Kim; Hyeongjun Im; Su Min Park; Kwang-Yeol Yang; Rae-Dong Jeong (Journal of Plant Pathology, 2021)

First report of cucumber mosaic virus infecting banana (Musa spp.) in Korea - Miah Bae; Hyo-Jeong Lee; Sangyeon Joo; Byungyeon Kim; Mi-Ri Park; Rae-Dong Jeong (Journal of Plant Pathology, 2021)

Role of p53 in transcriptional repression of SVCT2 - Eun Ho Kim; Dong-In Koh; Yea Seong Ryu; Sang-Soo Park; Seung-Woo Hong; Jai-Hee Moon; Jae-Sik Shin; Mi Jin Kim; Do Yeon Kim; Jun Ki Hong; Hong-Rae Jeong; Hyeseon Yun; et al. (Molecular Biology Reports, 2021)

First report of tomato spotted wilt virus infecting Cirsium setidens in Korea - Seongmu Mun; Su-Yeon Hwang; Na-Kyeong Kim; In-Sook Cho; Ho-Jong Ju; Rae-Dong Jeong (Journal of Plant Pathology, 2021)

First report of tobacco mosaic virus infecting Hosta longipes in Korea - Nam-Yeon Kim; Hyo-Jeong Lee; Na-Kyeong Kim; Hongsup Kim; Rae-Dong Jeong (Journal of Plant Pathology, 2021)

Tomato hairless on stems mutant affects trichome development - Won-Ki Hong; Jae-In Chun; Na-Rae Jeong; Heejin Kim; Jin-Ho Kang (Horticulture, Environment, and Biotechnology, 2021)

First report of cucumber mosaic virus infecting Aster scaber in Korea - Seoyeon Ko; Na-Kyeong Kim; Ji-Soo Park; Jin-Sung Hong; Rae-Dong Jeong (Journal of Plant Pathology, 2020)

First report of cucumber mosaic virus infecting Ledebouriella seseloides in Korea - Na-Kyeong Kim; Hyo-Jeong Lee; Hwi-Won Jeong; Seon-Min Go; Nam-Yeon Kim; Tae Ho Ryu; Sang-Yun Cho; Mi-Ri Park; Rae-Dong Jeong (Journal of Plant Pathology, 2020)

Sulfoquinovosylmonoacylglycerols regulating intestinal inflammation in co-culture system from the brown alga Turbinaria ornata - Seon Min Lee; Na-Hyun Kim; Yeong Kwang Ji; Yun Na Kim; You-Jin Jeon; Jeong Doo Heo; Eun Ju Jeong; Jung-Rae Rho (Algae, 2020)

Evaluation of Atmospheric Profile Retrieval Algorithm for GK2A Satellite with Dropsonde Observations - Tae-Myung Kim; Su Jeong Lee; Myoung-Hwan Ahn; Sung-Rae Chung (Asia-Pacific Journal of Atmospheric Sciences, 2020)

Dynamics of the gene regulatory networks of the inner and rosette leaves in Brassica rapa - Man-Sun Kim; Dongsan Kim; Seongmin Hong; Jeong-Rae Kim; Yong Pyo Lim (Horticulture, Environment, and Biotechnology, 2020)

First report of tobacco mosaic virus infectingHouttuynia cordata in Korea - Hyo-Jeong Lee; Hwi-Won Jeong; Seon-Min Go; Nam-Yeon Kim; Tae Ho Ryu; Na-Kyung Kim; Rae-Dong Jeong (Journal of Plant Pathology, 2019)

First report of tobacco mosaic virus infecting Geranium thunbergii in Korea - Hwi-Won Jeong; Seon-Min Go; Hyo-Jeong Lee; Nam-Yeon Kim; Mi-Ri Park; Rae-Dong Jeong (Journal of Plant Pathology, 2019)

First report of tobacco mosaic virus infecting Vitis coignetiae in Korea - Seon-Min Go; Hyo-Jeong Lee; Nam-Yeon Kim; Hwi-Won Jeong; Rae-Dong Jeong (Journal of Plant Pathology, 2019)

Full Thickness Skin Expansion ex vivo in a Newly Developed Reactor and Evaluation of Auto-Grafting Efficiency of the Expanded Skin Using Yucatan Pig Model - Man-Il Huh; Soo-Jin Yi; Kyung-Pil Lee; Hong Kyun Kim; Sang-Hyun An; Dan-Bi Kim; Rae-Hyung Ryu; Jun-Sik Kim; Jeong Ok Lim (Tissue Engineering and Regenerative Medicine, 2018)

First report of cucumber mosaic virus infecting pear in Korea - Hyo-Jeong Lee; Nam-Yeon Kim; Rae-Dong Jeong (Journal of Plant Pathology, 2018)

First Report of Infection of Fallopia multiflora with cucumber mosaic virus and zucchini yellow mosaic virus - Nam-Yeon Kim; Hyo-Jeong Lee; Mi-Ri Park; Jin-Sung Hong; Rae-Dong Jeong (Journal of Plant Pathology, 2018)

Effects of backcrossing on quality of strawberry fruit - Sun Yi Lee; Seung Yu Kim; Dae Young Kim; Ho Jeong Jeong; In Seok Um; Il Rae Rho (Horticulture, Environment, and Biotechnology, 2018)

Intraspecific variation of gene structure in the mitochondrial large subunit ribosomal RNA and cytochrome c oxidase subunit 1 of Pyropia yezoensis (Bangiales, Rhodophyta) - Il Ki Hwang; Seung-Oh Kim; Mi Sook Hwang; Eun-Jeong Park; Dong-Soo Ha; Sang-Rae Lee (Algae, 2018)

Mixotrophy in the sand-dwelling dinoflagellate Thecadinium kofoidii - Yeong Du Yoo; Kyeong Ah Seong; Jae Seong Kim; Seung Won Nam; Hae Jin Jeong; Jung-Rae Rho; Wonho Yih; Hyung Seop Kim (Marine Biology Research, 2018)

Genetic analysis of the tomato inquieta mutant links the ARP2/3 complex to trichome development - Na-Rae Jeong; Heejin Kim; In-Taek Hwang; Gregg A. Howe; Jin-Ho Kang (Journal of Plant Biology, 2017)

Behavioral responses of chinstrap and gentoo penguins to a stuffed skua and human nest intruders - Won Young Lee; Jin-Woo Jung; Han-Gu Choi; Hosung Chung; Yeong-Deok Han; Sam-Rae Cho; Jeong-Hoon Kim (Polar Biology, 2017)

Bioavailability of heavy metals in soils: definitions and practical implementation—a critical review - Rog-Young Kim; Jeong-Ki Yoon; Tae-Seung Kim; Jae E. Yang; Gary Owens; Kwon-Rae Kim (Environmental Geochemistry and Health, 2015)

Arteriovenous fistula stent infection diagnosed with radiolabelled leucocyte scintigraphy - Jeong Rae Yoo; Sang Taek Heo; Miyeon Kim; Hyun Woo Kim; Jee Won Chang; Heesung Song (Infectious Diseases, 2015)

Morphological and genetic variability among Ecklonia cava (Laminariales, Phaeophyceae) populations in Korea - Dong Mun Choi; Young Wook Ko; Rae-Seon Kang; Jeong Ha Kim (Algae, 2015)

Effect of the combined treatment with gamma irradiation and sodium dichloroisocyanurate on postharvest Rhizopus soft rot of sweet potato - Je-Yong Jeong; Min-Chul Yoon; Kwang-Youll Lee; Koo Jung; Hwa-Jung Kim; Hae-Jun Park; Rae-Dong Jeong (Journal of Plant Diseases and Protection, 2014)

Chlorophyll fluorescence as a diagnostic tool for abiotic stress tolerance in wild and cultivated strawberry species - Young-Wang Na; Ho Jeong Jeong; Sun-Yi Lee; Hyo Gil Choi; Seok-Hyeon Kim; Il Rae Rho (Horticulture, Environment, and Biotechnology, 2014)

Topical formulation of retinyl retinoate employing nanostructured lipid carriers - Sang Gon Lee; Jae Han Jeong; Sung Rae Kim; Kyung Min Lee; Byeong Kil Ahn; Mean Hyung Kang; Young Wook Choi (Journal of Pharmaceutical Investigation, 2012)

Allometric equations and biomass expansion factors of Japanese red pine on the local level - Choonsig Kim; Jaeyeob Jeong; Rae-Hyun Kim; Yeong-Mo Son; Kyeong Hak Lee; Jin-Seoung Kim; In-Hyeop Park (Landscape and Ecological Engineering, 2011)

Biomass and Carbon Storage in an Age-Sequence of Korean Pine (Pinus koraiensis) Plantation Forests in Central Korea - Xiaodong Li; Myong Jong Yi; Yowhan Son; Pil Sun Park; Kyeong Hak Lee; Yeong Mo Son; Rae Hyun Kim; Mi Jeong Jeong (Journal of Plant Biology, 2011)

Biomass Expansion Factors of Natural Japanese Red Pine (Pinus densiflora) Forests in Korea - Xiaodong Li; Myong Jong Yi; Yowhan Son; Pil Sun Park; Kyeong Hak Lee; Yeong Mo Son; Rae Hyun Kim; Mi Jeong Jeong (Journal of Plant Biology, 2010)

A volumetric study of the corpus callosum in 20s and 40s Korean people - Beob-Yi Lee; Jin-Hun Sohn; Mi-Hyun Choi; Su-Jeong Lee; Hyo-Seong Kim; Jae-Woong Yang; Jin-Seung Choi; Hyung-Sik Kim; Jeong-Han Yi; Gye-Rae Tack; Soon-Cheol Chung (Brain Structure and Function, 2009)

Observations of Forsythia koreana methanol extract on mast cell-mediated allergic reactions in experimental models - In-Young Choi; Phil-Dong Moon; Hyun-Na Koo; Noh-Yil Myung; Su-Jin Kim; Ji-Hyun Lee; Se-Hee Han; Goo Moon; Sung-Yum Seo; Hyun-Jea Sung; Rae-Kil Park; Hyun-Ja Jeong; et al. (In Vitro Cellular & Developmental Biology - Animal, 2007)

Low density lipoprotein inactivates Vibrio vulnificus cytolysin through the oligomerization of toxin monomer - Kwang-Hyun Park; Haet-Bit Yang; Hyung-Gue Kim; Young-Rae Lee; Hyoun Hur; Jong-Soo Kim; Bon-Sun Koo; Myung-Kwan Han; Jong-Hyun Kim; Young-Ju Jeong; Jong-Suk Kim (Medical Microbiology and Immunology, 2005)

Modelling summer extreme rainfall over the Korean peninsula using Wakeby distribution - Jeong‐Soo Park; Hyun‐Sook Jung; Rae‐Seon Kim; Jai‐Ho Oh (International Journal of Climatology, 2001)
Attempts to use the Wakeby distribution (WAD) with the method of L‐moments estimates (L‐ME), on the summer extreme rainfall data (time series of annual maximum of daily and 2‐day precipitation) at 61 gauging stations over South Korea have been made to obtain reliable quantile estimates for several return periods. The 90% confidence intervals for the quantiles determined by WAD have been obtained by the bootstrap resampling technique. The isopluvial maps of estimated design values corresponding to selected return periods have been presented. Copyright © 2001 Royal Meteorological Society

Morphological and genetic variability among Ecklonia cava (Laminariales, Phaeophyceae) populations in Korea - Dong Mun Choi; Young Wook Ko; Rae-Seon Kang; Jeong Ha Kim (Algae, 1970)